Eight countries improve MRV for climate change mitigation to better track Nationally Determined Contributions (NDC) mitigation targets (24% of total annual agriculture emissions) for agriculture. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Brazil, China, Colombia, Cuba, Ethiopia, Indonesia, Kenya, and Vietnam used CCAFS science and resources to improve national greenhouse gas estimates. Improved MRV enabled countries to set evidence-based mitigation targets in their domestic climate policies and nationally determined contributions (NDCs). Total agricultural emissions from these countries range from 1.4 to 1.9 GtCO2 yr-1 and six of the countries are among the top 20 GHG emitters in the livestock sector. More accurate monitoring supports better tracking and transparency of NDC mitigation targets.